Magnetic biomass charcoal nano polymer material for adsorbing heavy metals and preparation method of magnetic biomass charcoal nano polymer material
By dealing with biomass carbon nano -materials and specific compounds, the formation of magnetic biomass carbon nanimal polymer materials, solving the problem of low efficiency of existing biological carbon adsorption heavy metal ions, realizing efficient adsorption and rapid separation, reducing the water environment The risk of secondary pollution.
Patent Information
- Application Number
- CN202411522827.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-29
AI Technical Summary
When existing biomass charcoal adsorbs heavy metal ions, the adsorption amount and removal rate are low, and it is not easy to separate from water, which easily causes secondary pollution to the water environment.
By mixing the biomass carbon nanoma material with ultra -pure water, and adding six water -chloride, tetrashine metal chloride, and sodium mito water citrate citrate, forming a magnetic biomass carbon nano polymer material. This material realizes rapid solid solid solid separation through magnetic separation technology, and uses functional monomers of nitrogen, oxygen, and sulfur -sulfur groups in the polymer to improve the adsorption performance of heavy metal ions.
Achieve a magnetic biomass charcoal polymer material that is larger than the surface area, high selectivity and adsorption capacity, fast adsorption rate, and good recycling. risk.
Smart Images

Figure CN119368145A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedicine, and in particular relates to a magnetic biomass carbon nanopolymer material capable of absorbing heavy metals and a preparation method thereof. Background Art
[0002] With the rapid development of industrialization and the intensification of urbanization, a large amount of untreated or inadequately treated industrial wastewater, agricultural drainage containing heavy metals, urban sewage and leachate from landfills have further aggravated heavy metal pollution in the water environment. Therefore, it is of great significance to study the technology of removing heavy metal ions from water to reduce its harmful effects on the environment and ecology.
[0003] At present, common methods for removing heavy metal ions from wastewater include adsorption, electrochemical precipitation, membrane separation and ion exchange. Among them, the adsorption method is easy to operate, has high treatment efficiency, is economical and practical, and is considered to be a promising treatment technology. Biochar is a solid carbonaceous material made from biomass by pyrolysis at high temperature. It has a large specific surface area and developed porosity, and has been widely studied in the field of heavy metal ion adsorption. However, biochar can only rely on its own large specific surface energy to physically adsorb metal ions, and the adsorption amount and removal rate are low. In addition, biochar is not easy to separate from water, which can easily cause secondary pollution of the water environment, thus limiting the application of biochar. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a magnetic biomass carbon nanopolymer material for adsorbing heavy metals and a preparation method thereof. The prepared magnetic biomass carbon nanopolymer material has the characteristics of large specific surface area, high selectivity and adsorption capacity, fast adsorption rate and good recycling performance.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a magnetic biomass carbon nanopolymer material for adsorbing heavy metals, comprising the following steps:
[0007] S1. After mixing the biomass carbon nanomaterial with ultrapure water and performing ultrasonic dispersion, ferric chloride hexahydrate, ferrous chloride tetrahydrate and sodium citrate dihydrate are added and stirred to dissolve to obtain a mixed solution;
[0008] S2. heating the mixed solution and sequentially adjusting the pH, reacting at a constant temperature, cooling, magnetically separating, and washing to obtain a magnetic biomass carbon nanomaterial;
[0009] S3. Add magnetic biomass carbon nanomaterials and potassium persulfate to the aqueous phase A, and then add the oil phase B dropwise while stirring to carry out a first reaction at a constant temperature; after the reaction is completed, increase the temperature to carry out a second reaction, and after the reaction is completed, use a magnet to separate the solid and liquid to obtain a black solid powder;
[0010] S4. The black solid powder is crushed and washed with hot water several times, and then the residual suspension is removed by Soxhlet extraction with ethanol and ethanol-acetic acid solution respectively, and then filtered, washed and dried in sequence to obtain a magnetic biomass carbon nanopolymer material;
[0011] The preparation method of the aqueous phase A is as follows: polyvinyl alcohol and ultrapure water are mixed, stirred at a constant temperature until they are completely dissolved, and then sodium dodecyl sulfate and sodium sulfite are added, and the aqueous phase A is obtained after sufficient stirring;
[0012] The preparation method of the oil phase B is as follows: toluene, 2-thiophene carboxaldehyde, acrylamide, ethylene glycol dimethacrylate and ammonium persulfate are mixed, and the oil phase B is obtained by ultrasonically dissolving the mixture at a constant temperature.
[0013] Preferably, the preparation method of the biomass carbon nanomaterial is:
[0014] The dried biomass is carbonized at high temperature to obtain biomass carbon nanomaterials;
[0015] The biomass is one of yellow flower pineapple, crabapple flower, azalea, kapok flower, bauhinia flower, red cherry flower and reed flower; the high temperature carbonization temperature is 600-1000° C., and the high temperature carbonization time is 1-4 hours.
[0016] Preferably, the mass volume ratio of the biochar, ultrapure water, ferric chloride hexahydrate, ferrous chloride tetrahydrate and sodium citrate dihydrate in S1 is 0.1-1g:20-100mL:0.1-1g:0.05-0.5g:0.05-0.5g.
[0017] Preferably, the heating temperature in S2 is 40-90°C;
[0018] Adjust the pH value to 9-13, and the pH adjuster is 25% ammonia water;
[0019] The constant temperature reaction time is 0.5 to 12 hours.
[0020] Preferably, the mass volume ratio of the aqueous phase A, the magnetic biomass carbon nanomaterial, potassium persulfate and the oil phase B in S3 is: 100-400 mL: 0.4-4 g: 0.02-0.2 g: 3-6.5 mL.
[0021] Preferably, the stirring rate in S3 is 300-800 r / min;
[0022] The temperature of the first reaction is 30-70°C, and the time of the first reaction is 0.5-10h;
[0023] The temperature of the second reaction is 60 to 95° C., and the time of the second reaction is 2 to 24 hours.
[0024] Preferably, the volume ratio of ethanol to acetic acid in S4 is 1-10:1-10, and the Soxhlet extraction time is 5-48 hours.
[0025] Preferably, in the preparation method of the aqueous phase A, the mass volume ratio of polyvinyl alcohol, ultrapure water, sodium dodecyl sulfate and sodium sulfite is: 0.3-5 g: 50-500 mL: 1-8 g: 0.5-6 g.
[0026] The constant temperature is 55-95°C;
[0027] The stirring rate is 300-800 r / min, and the stirring time is 0.5-3 h.
[0028] Preferably, in the preparation method of the oil phase B, the volume mass ratio of toluene, 2-thiophenecarboxaldehyde, acrylamide, ethylene glycol dimethacrylate, and ammonium persulfate is 0.5-5 mL: 0.2-4 mL: 0.1-2.0 g: 0.2-4 mL: 0.02-0.2 g;
[0029] The constant temperature is 40-80°C.
[0030] In a second aspect, the present invention provides a magnetic biomass carbon nanopolymer material for adsorbing heavy metals, which is prepared by the above-mentioned preparation method.
[0031] Contains at least the following beneficial technical effects:
[0032] (1) The present invention has magnetically functionalized biochar, and can achieve rapid solid-liquid separation by applying an external magnetic field.
[0033] (2) The polymer synthesized by the present invention using 2-thiophene carboxaldehyde and acrylamide as functional monomers has a large number of nitrogen, oxygen and sulfur functional groups, strong coordination ability for metal ions, and improved adsorption performance for heavy metal ions.
[0034] (3) The adsorbent described in the present invention has a large specific surface area, high selectivity and adsorption capacity, fast adsorption rate and good recycling performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope image of the magnetic biomass carbon polymer material of Example 1;
[0036] Figure 2are infrared images of different materials, wherein: (a) is biochar, (b) is magnetic biochar, and (c) is the magnetic biochar polymer material of Example 1;
[0037] Figure 3 This is a graph showing the effect of adsorption time on adsorption amount of magnetic biomass carbon polymer material in Example 1;
[0038] Figure 4 This is a graph showing the effect of the initial concentration of heavy metal ions on the adsorption amount of the magnetic biomass carbon polymer material in Example 1;
[0039] Figure 5 This is a graph showing the effect of the number of recycling times of the magnetic biomass carbon polymer material on the adsorption rate in Example 1. DETAILED DESCRIPTION
[0040] The present invention provides a method for preparing a magnetic biomass carbon nanopolymer material for adsorbing heavy metals, comprising the following steps:
[0041] S1. After mixing the biomass carbon nanomaterial with ultrapure water and performing ultrasonic dispersion, ferric chloride hexahydrate, ferrous chloride tetrahydrate and sodium citrate dihydrate are added and stirred to dissolve to obtain a mixed solution.
[0042] In this step, the mass volume ratio of biochar, ultrapure water, ferric chloride hexahydrate, ferrous chloride tetrahydrate, and sodium citrate dihydrate is 0.1-1g: 20-100mL: 0.1-1g: 0.05-0.5g: 0.05-0.5g; more preferably 0.5g: 40mL: 0.35g: 0.185g: 0.139g. The present invention performs magnetic functionalization on biochar, giving biochar new magnetic properties, and can achieve rapid solid-liquid separation through an external magnetic field, avoiding the cumbersome and time-consuming traditional filtering or centrifugal methods, facilitating industrial production, and improving efficiency.
[0043] S2. heating the mixed solution and sequentially adjusting the pH, reacting at a constant temperature, cooling, magnetically separating, and washing to obtain a magnetic biomass carbon nanomaterial;
[0044] In this step, the heating temperature is 40-90° C.; the pH value is adjusted to 9-13, and the pH adjusting agent is 25% ammonia water; and the constant temperature reaction time is 0.5-12 hours.
[0045] S3. Add magnetic biomass carbon nanomaterials and potassium persulfate to the aqueous phase A, and then add the oil phase B dropwise while stirring to carry out a first reaction at a constant temperature; after the reaction is completed, increase the temperature to carry out a second reaction, and after the reaction is completed, use a magnet to separate the solid and liquid to obtain a black solid powder;
[0046] In this step, the mass volume ratio of the aqueous phase A, the magnetic biomass carbon nanomaterial, potassium persulfate, and the oil phase B is: 100-400 mL: 0.4-4 g: 0.02-0.2 g: 3-6.5 mL.
[0047] The stirring rate is 300-800 r / min;
[0048] The temperature of the first reaction is 30-70°C, and the time of the first reaction is 0.5-10h;
[0049] The temperature of the second reaction is 60 to 95°C, and the time of the second reaction is 2 to 24 hours;
[0050] The present invention adopts suspension polymerization method, uses magnetic biomass carbon as a matrix, 2-thiophene carboxaldehyde and acrylamide as functional monomers, and ethylene glycol dimethacrylate as a crosslinking agent to prepare magnetic biomass carbon polymer. The stabilizer effect of magnetic biomass carbon in the suspension polymerization process is utilized to prepare magnetic carbon nano polymer with uniform particle size distribution, good dispersibility and stability; the polymer synthesized using 2-thiophene carboxaldehyde and acrylamide as functional monomers has a large number of nitrogen, oxygen and sulfur functional groups, strong coordination ability to metal ions, and improved adsorption performance to heavy metal ions.
[0051] The preparation method of the aqueous phase A is as follows: polyvinyl alcohol and ultrapure water are mixed, stirred at a constant temperature until they are completely dissolved, and then sodium dodecyl sulfate and sodium sulfite are added, and the aqueous phase A is obtained after sufficient stirring;
[0052] In the preparation method of aqueous phase A, the mass volume ratio of polyvinyl alcohol, ultrapure water, sodium dodecyl sulfate and sodium sulfite is: 0.3-5 g: 50-500 mL: 1-8 g: 0.5-6 g.
[0053] The water phase of the present invention serves as a continuous phase and provides a dispersion medium for the oil phase, so that the oil phase is evenly dispersed in the water in the form of tiny droplets, which helps to improve the stability of the emulsion.
[0054] The constant temperature is 55-95°C;
[0055] The stirring rate is 300-800 r / min, and the stirring time is 0.5-3 h.
[0056] The preparation method of the oil phase B is as follows: toluene, 2-thiophene carboxaldehyde, acrylamide, ethylene glycol dimethacrylate and ammonium persulfate are mixed, and the oil phase B is obtained by ultrasonically dissolving the mixture at a constant temperature.
[0057] In the preparation method of oil phase B, the volume mass ratio of toluene, 2-thiophenecarboxaldehyde, acrylamide, ethylene glycol dimethacrylate, and ammonium persulfate is 0.5-5 mL: 0.2-4 mL: 0.1-2.0 g: 0.2-4 mL: 0.02-0.2 g;
[0058] The constant temperature is 40-80°C.
[0059] The present invention uses the oil phase as the dispersed phase, which can improve the solubility of the functional monomer and the crosslinking agent and promote the polymerization reaction. At the same time, the oil phase can also be used as a pore-forming agent. The product is washed with hot water and Soxhlet extracted with ethanol and ethanol-acetic acid solution to remove the residual suspension emulsion, and finally a porous polymer is obtained.
[0060] S4. The black solid powder is crushed and washed with hot water several times, and then the residual suspension is removed by Soxhlet extraction with ethanol and ethanol-acetic acid solution respectively, and then filtered, washed and dried in sequence to obtain a magnetic biomass carbon nanopolymer material;
[0061] In this step, the hot water temperature is preferably 50-80° C., and the washing times are 5 times; the black solid powder is first subjected to Soxhlet extraction with ethanol to remove the residual emulsion, and then subjected to Soxhlet extraction with ethanol-acetic acid solution to remove the residual emulsion. The emulsion is removed twice in succession more thoroughly, and the obtained product has higher purity.
[0062] The volume ratio of ethanol to acetic acid is 1-10:1-10, and the Soxhlet extraction time is 5-48 hours.
[0063] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0064] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0065] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the main idea or essential features of the present invention. Therefore, from all points of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any reference numerals in the claims should not be regarded as limiting the claims involved.
[0066] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.
[0067] It should also be understood that the specific embodiments described above are only used to explain the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, which should be covered by the protection scope of the present invention / invention.
[0068] Example 1
[0069] This embodiment provides a method for preparing a magnetic biomass carbon nanopolymer material for adsorbing heavy metals:
[0070] S1. The dried azalea was carbonized at 700°C for 2 h under nitrogen protection to obtain biomass carbon nanomaterials;
[0071] S2. After 0.5 g of biochar nanomaterial was mixed with 40 mL of ultrapure water and ultrasonically dispersed, 0.35 g of ferric chloride hexahydrate, 0.185 g of ferrous chloride tetrahydrate and 0.139 g of sodium citrate dihydrate were added and stirred to dissolve to obtain a mixed solution;
[0072] S3. After heating the mixed solution to 70°C, adjusting the pH to 11 with 25% ammonia water, stirring the mixture at a constant temperature for 3 hours, and then cooling it to room temperature, collecting the solid product by solid-liquid separation using a magnet, washing it with ultrapure water until it is neutral, and vacuum drying it at 60°C for 12 hours to obtain a magnetic biomass carbon nanomaterial;
[0073] S4. Prepare aqueous phase A solution: 1.0 g of polyvinyl alcohol and 200 mL of ultrapure water were mixed, stirred at 90 ° C at a stirring rate of 500 r / min until completely dissolved, and then 4.0 g of sodium dodecyl sulfate solution and 2.0 g of sodium sulfite were added, and the temperature was lowered to 45 ° C after stirring for 30 min;
[0074] Prepare oil phase B solution: mix 2.5 mL toluene, 1.2 mL 2-thiophenecarboxaldehyde, 0.57 g acrylamide, 1.0 mL ethylene glycol dimethacrylate and 0.04 g ammonium persulfate, and dissolve by ultrasonication at 60 °C;
[0075] 1.0 g of magnetic biomass carbon nanomaterials and 0.04 potassium persulfate were added to the aqueous phase A at 45 °C, and then 5.4 mL of the oil phase B was added dropwise at a stirring rate of 500 r / min to react for 1 h. After the reaction was completed, the temperature was raised to 85 °C for polymerization for 16 h. After the reaction was completed, a magnet was used for solid-liquid separation to obtain a black solid.
[0076] S5. The collected black solid was crushed, washed with 60°C hot water for 5 times, and then Soxhlet extracted with ethanol and ethanol-acetic acid solution (volume ratio of 9:1) for 24 hours to remove the residual suspension, and the product was collected by filtration, washed with ultrapure water for several times, and vacuum dried at 60°C for 12 hours to obtain magnetic biomass carbon nanopolymer material.
[0077] Example 2
[0078] This embodiment provides a method for preparing a magnetic biomass carbon nanopolymer material for adsorbing heavy metals:
[0079] S1. Carbonizing the dried kapok flowers at 700°C for 2 h under nitrogen protection to obtain biochar nanomaterials;
[0080] S2. After 0.5 g of biochar nanomaterial was mixed with 40 mL of ultrapure water and ultrasonically dispersed, 0.20 g of ferric chloride hexahydrate, 0.25 g of ferrous chloride tetrahydrate and 0.139 g of sodium citrate dihydrate were added and stirred to dissolve to obtain a mixed solution;
[0081] S3. After heating the mixed solution to 70°C, adjusting the pH to 11 with 25% ammonia water, stirring the mixture at a constant temperature for 3 hours, and then cooling it to room temperature, collecting the solid product by solid-liquid separation using a magnet, washing it with ultrapure water until it is neutral, and vacuum drying it at 60°C for 12 hours to obtain a magnetic biomass carbon nanomaterial;
[0082] S4. Prepare aqueous phase A solution: 0.8 g of polyvinyl alcohol and 200 mL of ultrapure water were mixed, stirred at 90 ° C at a stirring rate of 500 r / min until completely dissolved, and then 2.0 g of sodium dodecyl sulfate solution and 2.0 g of sodium sulfite were added, and the temperature was lowered to 45 ° C after stirring for 30 min;
[0083] Prepare oil phase B solution: mix 2.5 mL toluene, 1.2 mL 2-thiophenecarboxaldehyde, 0.57 g acrylamide, 1.0 mL ethylene glycol dimethacrylate and 0.04 g ammonium persulfate, and dissolve by ultrasonication at 60 °C;
[0084] 1.0 g of magnetic biomass carbon nanomaterial and 0.04 potassium persulfate were added to the above-mentioned 45°C aqueous phase A, and then 5.0 mL of oil phase B was added dropwise at a stirring rate of 500 r / min to react for 1 hour; after the reaction was completed, the temperature was raised to 85°C for polymerization reaction for 16 hours. After the reaction was completed, a magnet was used for solid-liquid separation to obtain a black solid.
[0085] S5. The collected black solid was crushed, washed with 50°C hot water for 5 times, and then Soxhlet extracted with ethanol and ethanol-acetic acid solution (volume ratio of 9:1) for 24 hours to remove the residual suspension, and the product was collected by filtration, washed with ultrapure water for several times, and vacuum dried at 60°C for 12 hours to obtain magnetic biomass carbon nanopolymer material.
[0086] Example 3
[0087] This embodiment provides a method for preparing a magnetic biomass carbon nanopolymer material for adsorbing heavy metals:
[0088] S1. The dried azalea was carbonized at 800°C for 2 h under nitrogen protection to obtain biomass carbon nanomaterials;
[0089] S2. After 0.5 g of biochar nanomaterial was mixed with 40 mL of ultrapure water and ultrasonically dispersed, 0.35 g of ferric chloride hexahydrate, 0.185 g of ferrous chloride tetrahydrate and 0.10 g of sodium citrate dihydrate were added and stirred to dissolve to obtain a mixed solution;
[0090] S3. After heating the mixed solution to 60°C, adjusting the pH to 10 with 25% ammonia water, stirring the mixture at a constant temperature for 3 hours, and then cooling it to room temperature, collecting the solid product by solid-liquid separation using a magnet, washing it with ultrapure water until it is neutral, and vacuum drying it at 60°C for 12 hours to obtain a magnetic biomass carbon nanomaterial;
[0091] S4. Prepare aqueous phase A solution: 1.0 g of polyvinyl alcohol and 200 mL of ultrapure water were mixed, stirred at 90 ° C at a stirring rate of 500 r / min until completely dissolved, and then 4.0 g of sodium dodecyl sulfate solution and 2.0 g of sodium sulfite were added, and the temperature was lowered to 45 ° C after stirring for 30 min;
[0092] Prepare oil phase B solution: mix 3.0 mL toluene, 1.0 mL 2-thiophenecarboxaldehyde, 0.57 g acrylamide, 1.0 mL ethylene glycol dimethacrylate and 0.04 g ammonium persulfate, and dissolve by ultrasonication at 60 °C;
[0093] 1.0 g of magnetic biomass carbon nanomaterial and 0.04 potassium persulfate were added to the above-mentioned 45°C aqueous phase A, and then 5.4 mL of oil phase B was added dropwise at a stirring rate of 500 r / min to react for 1 hour; after the reaction was completed, the temperature was raised to 70°C for polymerization reaction for 8 hours. After the reaction was completed, a magnet was used for solid-liquid separation to obtain a black solid.
[0094] S5. The collected black solid was crushed, washed with 80°C hot water for 5 times, and then Soxhlet extracted with ethanol and ethanol-acetic acid solution (volume ratio of 8:2) for 24 hours to remove the residual suspension, and the product was collected by filtration, washed with ultrapure water for several times, and vacuum dried at 60°C for 12 hours to obtain magnetic biomass carbon nanopolymer material.
[0095] Example 4
[0096] This embodiment provides a method for preparing a magnetic biomass carbon nanopolymer material for adsorbing heavy metals:
[0097] S1. Carbonizing the dried Bauhinia flowers at 700°C for 2 h under nitrogen protection to obtain biochar nanomaterials;
[0098] S2. After 0.1 g of biochar nanomaterial was mixed with 20 mL of ultrapure water and ultrasonically dispersed, 0.1 g of ferric chloride hexahydrate, 0.05 g of ferrous chloride tetrahydrate and 0.05 g of sodium citrate dihydrate were added and stirred to dissolve to obtain a mixed solution;
[0099] S3. After heating the mixed solution to 40°C, adjusting the pH to 9 with 25% ammonia water, stirring the mixture at a constant temperature for 0.5h, and then cooling it to room temperature, collecting the solid product by solid-liquid separation using a magnet, washing it with ultrapure water until it is neutral, and vacuum drying it at 60°C for 12h to obtain a magnetic biomass carbon nanomaterial;
[0100] S4. Prepare aqueous phase A solution: Mix 0.3 g of polyvinyl alcohol and 50 mL of ultrapure water, stir at 55 ° C at a stirring rate of 300 r / min until completely dissolved, then add 1.0 g of sodium dodecyl sulfate solution and 0.5 g of sodium sulfite, stir for 30 min and then reduce the temperature to 30 ° C;
[0101] Prepare oil phase B solution: mix 0.5 mL toluene, 0.2 mL 2-thiophenecarboxaldehyde, 0.1 g acrylamide, 0.2 mL ethylene glycol dimethacrylate and 0.02 g ammonium persulfate, and dissolve by ultrasonication at 40 °C;
[0102] 0.4 g of magnetic biomass carbon nanomaterials and 0.02 potassium persulfate were added to the aqueous phase A at 30 °C, and then 3 mL of the oil phase B was added dropwise at a stirring rate of 500 r / min to react for 1 h. After the reaction was completed, the temperature was raised to 60 °C for polymerization for 2 h. After the reaction was completed, a magnet was used for solid-liquid separation to obtain a black solid.
[0103] S5. The collected black solid was crushed, washed with 60°C hot water for 5 times, and then Soxhlet extracted with ethanol and ethanol-acetic acid solution (volume ratio of 1:1) for 24 hours to remove the residual suspension, and the product was collected by filtration, washed with ultrapure water for several times, and vacuum dried at 60°C for 12 hours to obtain magnetic biomass carbon nanopolymer material.
[0104] Example 5
[0105] This embodiment provides a method for preparing a magnetic biomass carbon nanopolymer material for adsorbing heavy metals:
[0106] S1. The dried reed flowers were carbonized at 700°C for 2 h under nitrogen protection to obtain biomass carbon nanomaterials;
[0107] S2. After 1 g of biochar nanomaterial was mixed with 100 mL of ultrapure water and ultrasonically dispersed, 1 g of ferric chloride hexahydrate, 0.5 g of ferrous chloride tetrahydrate and 0.5 g of sodium citrate dihydrate were added and stirred to dissolve to obtain a mixed solution;
[0108] S3. After heating the mixed solution to 90°C, adjusting the pH to 13 with 25% ammonia water, stirring the mixture at a constant temperature for 12 hours, and then cooling it to room temperature, collecting the solid product by solid-liquid separation using a magnet, washing it with ultrapure water until it is neutral, and vacuum drying it at 60°C for 12 hours to obtain a magnetic biomass carbon nanomaterial;
[0109] S4. Prepare aqueous phase A solution: 5 g of polyvinyl alcohol and 500 mL of ultrapure water were mixed, stirred at 95 ° C at a stirring rate of 800 r / min until completely dissolved, and then 8.0 g of sodium dodecyl sulfate solution and 6 g of sodium sulfite were added, and the temperature was lowered to 70 ° C after stirring for 3 h;
[0110] Prepare oil phase B solution: mix 5 mL toluene, 4 mL 2-thiophenecarboxaldehyde, 2.0 g acrylamide, 4 mL ethylene glycol dimethacrylate and 0.2 g ammonium persulfate, and dissolve by ultrasonication at 80 °C;
[0111] 4 g of magnetic biomass carbon nanomaterials and 0.2 potassium persulfate were added to the aqueous phase A at 70 °C, and then 6.5 mL of the oil phase B was added dropwise at a stirring rate of 800 r / min to react for 10 h. After the reaction was completed, the temperature was raised to 95 °C for polymerization for 24 h. After the reaction was completed, a magnet was used for solid-liquid separation to obtain a black solid.
[0112] S5. The collected black solid was crushed, washed with 60°C hot water for 5 times, and then Soxhlet extracted with ethanol and ethanol-acetic acid solution (volume ratio of 1:10) for 24 hours to remove the residual suspension, and the product was collected by filtration, washed with ultrapure water for several times, and vacuum dried at 60°C for 12 hours to obtain magnetic biomass carbon nanopolymer material.
[0113] Comparative Example 1
[0114] In this comparative example, a magnetic biomass carbon nanomaterial was obtained according to steps S1 to S3 of Example 1, and then 1.0 g of the magnetic biomass carbon nanomaterial was mixed with 1.2 mL of 2-thiophenecarboxaldehyde, 0.57 g of acrylamide, 1.0 mL of ethylene glycol dimethacrylate, and 50 mL of ultrapure water. After ultrasonic dissolution, the mixture was heated to 85°C for polymerization for 16 h. After the reaction was completed, a magnet was used for solid-liquid separation to obtain a black solid. The solid was washed with ethanol and ultrapure water for 5 times, respectively, and dried in vacuo at 60°C for 12 h to obtain a magnetic biomass carbon nanopolymer material.
[0115] Comparative Example 2
[0116] In this comparative example, magnetic biomass carbon nanomaterials were obtained according to steps S1 to S3 of Example 1.
[0117] Experimental Example 1
[0118] The magnetic biomass carbon nanopolymer material prepared in Example 1 was characterized:
[0119] 1. Scanning Electron Microscope Characterization
[0120] The magnetic biomass carbon nanopolymer material prepared in Example 1 was characterized by scanning electron microscopy. The characterization results are shown in the attached Figure 1 .Depend on Figure 1 It can be clearly observed that the material is in the shape of irregular layered particles with a rough surface and good dispersibility. There are a large number of gaps between the particles. This multi-void structure is conducive to accelerating mass transfer.
[0121] 2. Infrared spectroscopy characterization
[0122] The magnetic biomass carbon nanopolymer material prepared in Example 1 was characterized by infrared spectroscopy. The characterization results are shown in the attached figure. Figure 2 As shown. Biomass charcoal map (attached Figure 2 a) at 3300cm -1 The broad peak at 1638 cm is the -OH stretching vibration peak. -1 The stretching vibration peaks are attributed to C=O; Figure 2 b Magnetic biochar and Figure 3 The magnetic biomass carbon nanopolymer material spectrum of c can be observed at 567-580cm -1The Fe-O characteristic peaks at 1000 nm indicate that ferroferric oxide is embedded in biochar and polymer. In addition, the magnetic biochar nanopolymer material spectrum (Appendix Figure 3 c) at 1088cm -1 The broad peak at 1394 cm is attributed to the stretching vibration peaks of COC, CS, and OH. -1 The peak at 1628cm is attributed to the characteristic absorption peak of CH2. -1 The strong broad peak at 3183 cm is attributed to the stretching vibration of -NH2, -C=C, -C=N, and -C=O. -1 -CH=C stretching vibration peak on the thiophene ring, 3300-3550cm -1 The strong absorption peaks in the range are the stretching vibration peaks of -OH and -NH2. The above results confirm that thiophene carboxaldehyde and acrylamide as bifunctional monomers have a cross-linking reaction with ethylene glycol dimethacrylate, indicating that the magnetic biomass carbon nanopolymer material has been successfully synthesized.
[0123] 3. Dynamic adsorption performance study
[0124] 15 mg of the magnetic biomass carbon nanopolymer adsorbent prepared in Example 1 was dispersed in 10 mL of 400 mg / L Zn 2+ 、Cd 2+ and Pb 2+ The adsorbent was placed in a mixed solution (pH 6.0) at 25°C and oscillated at a speed of 100 r / min for 0 to 60 min, and a magnet was used for solid-liquid separation. The content of metal ions in the solution was determined by graphite furnace atomic absorption spectrometry, and the adsorption amount Q of the adsorbent for metal ions was calculated according to the following formula (1).
[0125]
[0126] Where: c0 and c t are the initial concentration of metal ions in the solution and the concentration at the adsorption time t, mg / L; v is the volume of the solution, mL; m is the weight of the adsorbent, g.
[0127] With adsorption time t as the horizontal axis and adsorption amount Q as the vertical axis, the adsorption kinetic curve of the adsorption material for metal ions is drawn. The results are shown in the attached Figure 3 As can be seen from the figure, when the adsorption time is 20min, the adsorbent has a strong affinity for Zn 2+ 、Cd 2+ and Pb 2+ The adsorption of 2-hydroxy-2-nitropropene tended to saturation, and the maximum adsorption amounts were 240.0, 204.6 and 139.6 mg / g, respectively. The pseudo-first-order kinetic model and pseudo-second-order kinetic model were used to fit the kinetic data. The results showed that the correlation coefficient (R 2greater than 0.999) is much larger than the pseudo-first-order kinetic model. Moreover, the pseudo-second-order kinetic model fitting curve yields Zn 2+ 、Cd 2+ , Pb 2 + The equilibrium adsorption capacity of Zn was 246.3, 209.2, and 144.9 mg / g, which was consistent with the actual test results. 2+ 、Cd 2+ , Pb 2+ The adsorption capacities (240.0, 204.6, and 139.6 mg / g) are very close, indicating that the adsorbents are very suitable for Zn 2+ 、Cd 2+ and Pb 2+ The adsorption behavior conforms to the pseudo-second-order kinetic model. During the adsorption process, the adsorption rate is mainly controlled by chemical interactions.
[0128] 4. Study on static adsorption performance
[0129] 15 mg of the magnetic biomass carbon nanopolymer adsorbent prepared in Example 1 was dispersed in 10 mL of Zn with a concentration of 50 to 1000 mg / L. 2+ 、Cd 2+ and Pb 2+ The mixed solution (pH 6.0) was adsorbed at 25°C and 100 r / min for 1 hour, and the solid-liquid separation was performed using a magnet. The metal ion content in the solution after adsorption equilibrium was determined by graphite furnace atomic absorption spectrometry, and the adsorption amount of the adsorbent on the metal ions was calculated. Figure 4 The figure shows the effect of initial metal ion concentration on adsorption. Figure 4 It can be seen that when the initial concentration increases to 600 mg / L, the adsorption tends to saturation. The adsorption isotherms of the three metal ions in the adsorbent were fitted by Langmuir and Freundlich models. The results show that the correlation coefficient R of the linear equation fitting of the Langmuir model is 2 The value is higher than that fitted by the linear equation of the Freundlich model, indicating that the Langmuir adsorption isotherm is more suitable for describing the Zn 2+ 、Cd 2+ and Pb 2+ The adsorption behavior of Zn on magnetic biomass carbon nanopolymer adsorbent. Therefore, it can be inferred that the adsorption behavior is monolayer type, which includes physical and chemical adsorption mechanisms. In addition, the Langmuir adsorption model was used to calculate the adsorption behavior of Zn 2+ 、Cd 2+ and Pb 2+ The maximum adsorption capacities are 349.65, 256.41, and 180.83 mg / g, respectively, which are close to the experimental values of 343.3, 250.7, and 177.6 mg / g.
[0130] The static adsorption test was used to determine the adsorption of Zn by the adsorbents obtained in Examples 2 to 5 and Comparative Examples 1 to 2. 2+ 、Cd 2+ and Pb 2+ The maximum adsorption capacity of
[0131]
[0132] 5. Recyclability
[0133] 15 mg of the magnetic biomass carbon nanopolymer adsorbent prepared in Example 1 was dispersed in 10 mL of 300 mg / L Zn 2+ 、Cd 2+ and Pb 2+ The adsorbent was placed in a mixed solution (pH 6.0) at 25°C and 100 r / min for 1 hour, and then separated by a magnet to determine the adsorption capacity. The separated adsorbent was eluented with 200 mL of 0.1 mol / L EDTA solution and ultrasonicated for 30 minutes to remove metal ions, which was repeated twice. It was washed several times with ultrapure water, dried, and then recycled. The results are shown in the figure. Figure 5 After 6 adsorption-desorption cycles, the adsorbent has a strong affinity for Zn 2+ 、Cd 2+ and Pb 2+ The adsorption amount still reached more than 81% of the initial value, indicating that the adsorbent has good reusability.
[0134] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a magnetic biomass carbon nanopolymer material for adsorbing heavy metals, characterized in that: The following steps are involved: S1. After mixing the biomass carbon nanomaterial with ultrapure water and performing ultrasonic dispersion, ferric chloride hexahydrate, ferrous chloride tetrahydrate and sodium citrate dihydrate are added and stirred to dissolve to obtain a mixed solution; S2. heating the mixed solution and sequentially adjusting the pH, reacting at a constant temperature, cooling, magnetically separating, and washing to obtain a magnetic biomass carbon nanomaterial; S3. Add magnetic biomass carbon nanomaterials and potassium persulfate to the aqueous phase A, and then add the oil phase B dropwise while stirring to carry out a first reaction at a constant temperature; after the reaction is completed, increase the temperature to carry out a second reaction, and after the reaction is completed, use a magnet to separate the solid and liquid to obtain a black solid powder; S4. The black solid powder is crushed and washed with hot water several times, and then the residual suspension is removed by Soxhlet extraction with ethanol and ethanol-acetic acid solution respectively, and then filtered, washed and dried in sequence to obtain a magnetic biomass carbon nanopolymer material; The preparation method of the aqueous phase A is as follows: polyvinyl alcohol and ultrapure water are mixed, stirred at a constant temperature until they are completely dissolved, and then sodium lauryl sulfate and sodium sulfite are added, and the aqueous phase A is obtained after sufficient stirring; The preparation method of the oil phase B is as follows: toluene, 2-thiophene carboxaldehyde, acrylamide, ethylene glycol dimethacrylate and ammonium persulfate are mixed, and the oil phase B is obtained by ultrasonically dissolving the mixture at a constant temperature.
2. The preparation method according to claim 1, characterized in that: The preparation method of the biomass carbon nanomaterial is: The dried biomass is carbonized at high temperature to obtain biomass carbon nanomaterials; The biomass is one of yellow flower pineapple, crabapple flower, azalea, kapok flower, bauhinia flower, red cherry flower and reed flower; the high temperature carbonization temperature is 600-1000° C., and the high temperature carbonization time is 1-4 hours.
3. The preparation method according to claim 1, characterized in that: The mass volume ratio of the biochar, ultrapure water, ferric chloride hexahydrate, ferrous chloride tetrahydrate, and sodium citrate dihydrate in the S1 is 0.1-1 g: 20-100 mL: 0.1-1 g: 0.05-0.5 g: 0.05-0.5 g.
4. The preparation method according to claim 1, characterized in that: The heating temperature in S2 is 40-90° C.; Adjust the pH value to 9-13, and the pH adjuster is 25% ammonia water; The constant temperature reaction time is 0.5 to 12 hours.
5. The preparation method according to claim 1, characterized in that: The mass volume ratio of the water phase A, the magnetic biomass carbon nanomaterial, potassium persulfate and the oil phase B in the S3 is: 100-400 mL: 0.4-4 g: 0.02-0.2 g: 3-6.5 mL.
6. The preparation method according to claim 1, characterized in that: The stirring rate in S3 is 300-800 r / min; The temperature of the first reaction is 30-70°C, and the time of the first reaction is 0.5-10h; The temperature of the second reaction is 60 to 95° C., and the time of the second reaction is 2 to 24 hours.
7. The preparation method according to claim 1, characterized in that: The volume ratio of ethanol to acetic acid in S4 is 1-10:1-10, and the Soxhlet extraction time is 5-48 hours.
8. The preparation method according to claim 1, characterized in that: In the preparation method of the aqueous phase A, the mass volume ratio of polyvinyl alcohol, ultrapure water, sodium dodecyl sulfate and sodium sulfite is: 0.3-5g: 50-500mL: 1-8g: 0.5-6g. The constant temperature is 55-95°C; The stirring rate is 300-800 r / min, and the stirring time is 0.5-3 h.
9. The preparation method according to claim 1, characterized in that: In the preparation method of the oil phase B, the volume mass ratio of toluene, 2-thiophenecarboxaldehyde, acrylamide, ethylene glycol dimethacrylate, and ammonium persulfate is 0.5-5 mL: 0.2-4 mL: 0.1-2.0 g: 0.2-4 mL: 0.02-0.2 g; The constant temperature is 40-80°C.
10. A magnetic biomass carbon nanopolymer material for adsorbing heavy metals, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Phthalocyanine crystal, electrophotographic photoreceptor utilizing the same, electrophotographic photoreceptor cartridge and image forming apparatus
CN101405349A
Preparation method of modified biomass charcoal composite chitosan-based adsorbent
CN113663654A
Magnetic biochar as well as preparation method and application thereof
CN118719000A
Cited By
Method for removing readily carbonizable substances of sodium citrate based on green chemistry
CN120817854A